RELATIONSHIP OF MORPHOLOGICAL QUALITY AND MOTOR SKILLS WITH THE RESULTS SITUATION-MOTOR TESTS IN FOOTBALL - Vidosav Lolić; Osmo Bajrić; Dejan Lolić; Slobodan Goranović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The study was conducted on a sample of 137 soccer players aged 14-16 years from the football clubs of the Central Canton of the Federation of BiH, who plays for his teamin the cadet category of the Youth League of BiH. Thestudywasperformed 9 variables was appliedto assess themorphological characteristics, 15 variables for the assessment offundamental motor skills and 12 variables for the evaluation of situational -motor skills. The main objective of this study was to determine the degree of correlation between morphological characteristics and basic motor skills with the results of situational- motor tests in football. To confirmthecorrelationbetween morphological characteristics and basic motorskills isa result of situational-motor tests in football has been applied to classical canonical correlation analysis (Bonacin 2010). Analysisoftheresults ofcanonical correlation analysis revealed that the investigatedproperties associated with three pairs of canonical factors statistically significant level of .001.